In vitro regeneration of shoot segments of Manihot esculenta varieties cultivated in northern Brazil - Costa, Milla Corrêa; Pletsch Dalla Costa, Tanara; de Freitas Sia, Eliandra; Rangel Rodrigues, Rogério; Miléo da Silva, Ana Caroline (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
The objective of this work was to evaluate the in vitro establishment of BRS Kiriris, BRS Poti, Água Morna, Paraná and Jurará of Manihot esculenta varieties. For this purpose, the shoot apices were inoculated in test tubes containing five mL of MS medium, supplemented with 0.02 mg/L naphthaleneacetic acid (NAA), 0.04 mg/L of 6-benzylaminopurine (BAP) and 0.05 mg/L of gibberellic acid (GA3). The experimental design was completely randomized (CRD), with five varieties and six replicates, where each replicate consisted of five tubes containing one explant, totaling 30 explants per treatment. The number of explants contaminated by fungus and/or bacteria and necrosis were evaluated every seven days. After 30 days of in vitro culture, the following variables were evaluated: survival, mortality, seedling height, number of green leaves, number of roots and length of the largest root. The data concerning the analyzed variables were transformed to √(x + 0.5) and then subjected to Analysis of Variance. The averages were compared using the Tukey test at 5% probability using the statistical program Sisvar 5.6. According to the results obtained, the BRS Poti variety obtained lower contamination rate and greater in vitro survival in relation to the other varieties. The Jurará variety showed the best results in the development of aerial part and root system in vitro. On the other hand, the Paraná variety did not obtain satisfactory results for the in vitro establishment. Index terms: Cassava; growth regulators; in vitro culture.